Enabling Cysteine‐Free Native Chemical Ligation at Challenging Junctions with a Ligation Auxiliary Capable of Base Catalysis. Issue 35 (29th July 2021) - Fuchs, Olaf; Trunschke, Sebastian; Hanebrink, Hendrik; Reimann, Marc; Seitz, Oliver
Abstract: Ligation auxiliaries are used in chemical protein synthesis to extend the scope of native chemical ligation (NCL) beyond cysteine. However, auxiliary‐mediated ligations at sterically demanding junctions have been difficult. Often the thioester intermediate formed in the thiol exchange step of NCL accumulates because the subsequent S→N acyl transfer is extremely slow. Here we introduce the 2‐mercapto‐2‐(pyridin‐2‐yl)ethyl (MPyE) group as the first auxiliary designed to aid the ligation reaction by catalysis. Notably, the MPyE auxiliary provides useful rates even for junctions containing proline or a β‐branched amino acid. Quantum chemical calculations suggest that the pyridine nitrogen acts as an intramolecular base in a rate‐determining proton transfer step. The auxiliary is prepared in two steps and conveniently introduced by reductive alkylation. Auxiliary cleavage is induced upon treatment with TCEP/morpholine in presence of a Mn II complex as radical starter. The synthesis of a de novo designed 99mer peptide and an 80 aa long MUC1 peptide demonstrates the usefulness of the MPyE auxiliary. Abstract : The MPyE group is the first sulfur based auxiliary enabling peptide ligation at proline and β‐branched amino acids. The pyridine nitrogen probably acts as a base that catalyzes the S→N acyl transfer during native chemical ligation.